Penggunaan Facebook di kalangan pelajar lelaki dan perempuan pada sekolah menengah di zon Petaling Jaya Selatan - Abd. Hamid, Norhazlina; Mohd Ayub, Ahmad Fauzi; Zainal Abiddin, Norhasni (Kopertis Wilayah VI Jawa Tengah, 2011)
Internet technology has brought about a significant impact for the world at large and provide many benefits to its users. At the very beginning, internet technology may be used to get varieties of information and nowadays it being used as a social networking site. It started with the present of many social sites especially Facebook. This study involved 300 students from three secondary schools in Petaling Jaya Selatan zone, Selangor, Malaysia. The objectives of this study is to identify the Facebook used among male and female students in secondary school. This article concerns about for what purpose is Facebook used; how often do respondents access Facebook; and what activities do they do in Facebook? Result shows that there are no significant differences in Facebook used among male and female students. Results also reveal that students spent at least one hour per day for Facebook used. This study recommends that parents should closely monitor their children in dealing with Facebook issues.